Joy at the Birth of Christ: A Study of Matthew 2:10 and Luke 2:10 - Nagy, József (The Biblical Annals, 2025)
The infancy narratives in Matthew and Luke present a mix of similarities and differences, creating challenges for scholars investigating the origins of the Synoptic Gospels and conducting comparative studies. This paper contends that the parallels between the two accounts are not coincidental, proposing that, even under cautious assumptions, they likely stem from a shared source. Exegetes continue to debate the extent of these parallels between Matt 1–2 and Luke 1–2, including the potential connection between Matt 2:10 and Luke 2:10. This study argues that the unifying theme in these verses is joy. Additionally, some minor parallels can also be identified. These similarities can be justified by looking at the texts in their context. In recent years, some scholars have studied the phenomenon of joy in Luke-Acts. Besides relying on these works to explore Luke 2:10, this paper seeks to provide new insights. The analysis of joy in Matthew is itself a fresh approach, as it has received little attention. This is particularly evident in the case of Matt 2:10, which is often overlooked or mentioned only in passing by commentators.